Review of islanding detection schemes for utility interactive solar photovoltaic systems. Issue 3 (19th February 2022) - Gupta, Nikita; Dogra, Rahul; Garg, Rachana; Kumar, Parmod
ABSTRACT: The shift to renewable energy sources has proved to be a feasible alternative to satisfy the increasing energy needs of the developing world, significantly reducing the dependence on conventional energy sources without degrading the environment. Solar energy, in particular, remains one of the best available renewable energy source choices because it is abundant, clean and efficient. Solar photovoltaic (PV) technology directly converts solar energy into electric power. However, owing to intermittent nature of solar energy, electric energy storage or utility interaction is an indispensable component of solar PV systems. Utility interconnection calls for many issues like synchronization, power quality, reactive power management, and islanding. Among these issues, islanding detection is one of the most critical aspects of interconnecting distributed generation (DG) such as PV system to the utility. Islanding detection schemes may usually be categorized as remote schemes associated with utility-side islanding detection, local schemes associated with DG-side islanding detection, or the new advanced signal processing-based schemes. This paper presents an analysis of different islanding detection schemes and their benefits and limitations. A summary table that compares and contrasts the existing schemes is also presented.